7. On priority of "Genistion purgantis" Tüxen in Tüxen & Oberdorfer 1958 and "Senecioni-Genistetum purgantis" Tüxen & Oberdorfer 1958 - Rivas-Martínez, Salvador; Fernández-González, Federico (Lazaroa, 2014)
In a recent review of which we were co-authors (Rivas-Martínez, Belmonte, Cantó, Fernández-González, Fuente, Moreno, Sánchez-Mata & Sancho, Lazaroa 7: 93-124. 1987), rejection of names Genistion purgantis Túxen in Túxen & Oberdorfer 1958 [Veróff. Geobot. Inst. Rúbel Zúrich 32: 228] and Senecio tournefortii-Genistapurgans Ass. Túxen & Oberdorfer 1958 [op. cit.: 229-230] versus Pino-Cytision purgantis Rivas-Martínez 1964 [Anales lnst. Bot. Cavanilles 22: 358] and Junipero nanae-Sarothamnetum purgantis Rivas-Martínez 1963 [Anales Inst. Bot. Cavanilles 21(1): 172-186] respectively, was proposed and adopted.